Interactions of mucins with the Tn or Sialyl Tn cancer antigens including MUC1 are due to GalNAc–GalNAc interactions - Haugstad, Kristin E (Glycobiology, 2016)
The molecular mechanism(s) underlying the enhanced self-interactions of mucins possessing the Tn (GalNAcα1-Ser/Thr) or STn (NeuNAcα2-6GalNAcα1-Ser/Thr) cancer markers were investigated using optical tweezers (OT). The mucins examined included modified porcine submaxillary mucin containing the Tn epitope (Tn-PSM), ovine submaxillary mucin with the STn epitope (STn-OSM), and recombinant MUC1 analogs with either the Tn and STn epitope. OT experiments in which the mucins were immobilized onto polystyrene beads revealed identical self-interaction characteristics for all mucins. Identical binding strength and energy landscape characteristics were also observed for synthetic polymers displaying multiple GalNAc decorations. Polystyrene beads without immobilized mucins showed no self-interactions and also no interactions with mucin-decorated polystyrene beads. Taken together, the experimental data suggest that in these molecules, the GalNAc residue mediates interactions independent of the anchoring polymer backbone. Furthermore, GalNAc–GalNAc interactions appear to be responsible for self-interactions of mucins decorated with the STn epitope. Hence, Tn-MUC1 and STn-MUC1 undergo self-interactions mediated by the GalNAc residue in both epitopes, suggesting a possible molecular role in cancer. MUC1 possessing the T (Galβ1-3GalNAcα1-Ser/Thr) or ST antigen (NeuNAcα2-3Galβ1-3GalNAcα1-Ser/Thr) failed to show self-interactions. However, in the case of ST-MUC1, self-interactions were observed after subsequent treatment with neuraminidase and β-galactosidase. This enzymatic treatment is expected to introduce Tn-epitopes and these observations thus further strengthen the conclusion that the observed interactions are mediated by the GalNAc groups.